Hubble Bubble Equals Trouble: The Hazards of Water Pipe Smoking - Jacob Urkin; Rivka Ochaion; Aya Peleg (The Scientific World Journal)
A Narghile, one of the names for a water pipe, is an instrument for tobacco smoking that has became a trend among the youth in Israel. The mistaken opinion that smoking a Narghile is not as dangerous as smoking cigarettes makes the youngsters and their parents take it lightly and contributes to the expansion of its use. The objective of this paper was to review the literature on the health risks of Narghile smoking. A literature search of Medline (PubMed) and the Internet on the health hazards of Narghile smoking was conducted. The health hazards that the Narghile smoker is exposed to include interference with oxidation, damage to genetic compounds, increased risk of developing malignancies, infectious diseases, damage to the fetus and newborn, and exposure to commonly abused chemicals. It is concluded that increased awareness of the expanded use of the Narghile is imperative and education programs about the prevention of cigarette smoking and substance abuse should also include Narghile smoking.